Stock market perceptions of the motives for mergers in cases reviewed by the UK competition authorities - Arnold, Malcolm F.; Parker, David (John Wiley & Sons, Ltd, 2008)
A number of studies have considered the motivation of managers to follow a merger strategy. However, as far as we are aware none has looked at the influence of competition regulation on merger motives using stock market data and event study techniques. Data drawn from 63 merger cases in the UK between 1989 and 2003 are examined for the stock market's perceptions of what motivated managers to pursue their initial merger bid. The findings suggest that the Synergy and Hubris dominate as motivations for mergers and that, unintentionally, competition policy may help to reduce the number of mergers motivated by Managerialism.